FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI DESA KUALU KECAMATAN TAMBANG KAMPAR - S, Putri Wulandini; Saputra, Roni (Sistem Informasi, 2018)
Clean and Healthy Behavior/ PHBS is all health behavior that is done on the basis of awareness so that family members can help themselves in the health field. Health is a treasure that is priceless and to get health is willing to spend excessive funds. Based on the profile of Dinas Kesehatan Provinsi Riau the percentage of PHBS at home is 49,5%. Nevertheless, the implementation of PHBS in Rural areas remains a highlight and an ongoing program for the Government and District Health Offices. The purpose of this study was to find out "Factors Associated With Healthy Behavior Clean and Healthy (Phbs) In Village Kualu Kampar Sub-District ". The type of quantitative research with correlation design, with a population of 350 heads of households, and a sample of 100 people, the sampling technique is Probability Sampling. Data collection using questionnaire. Data analysis was done univariat and bivariate. The result of the research on the knowledge of the respondents about PHBS in the household is good, that is 64% of the education of the majority respondent of middle level (SMA) 59%, the role of health workers in PHBS is less the role that is 54%, the role of public figure is good that is56% PHBS is 51%. Bivariate results obtained pvalue 0.01 educational factors and 0.006 knowledge factor, which means there is a relationship. While the role factor Nakes p value 0.81 and the role of Toma 0.151, which means no relationship. From this research, it is expected that the participation of health personnel to provide complete information through the extension to the community about PHBS in Household.